2021
DOI: 10.1039/d0ta11648c
|View full text |Cite
|
Sign up to set email alerts
|

An extended carbonyl-rich conjugated polymer cathode for high-capacity lithium-ion batteries

Abstract: A novel polymer with an extended π-conjugated structure (PPh-PTO) can show a delocalized electronic distribution and achieve a higher voltage, excellent cycle life, and good rate capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 31 publications
4
52
0
Order By: Relevance
“…In addition, a new peak at 289.9 eV assigned to C−Li bond emerges, which may be originated from the lithiation reaction or Li + ion insertion in condensed aromatic structures. Meanwhile, three peaks are also observed in the O1s spectrum (Figure 6b), corresponding to O−Li (531.1 eV), C−O (532.2 eV) and C=O (533.5 eV), respectively, [5a] further suggesting the formation of lithium enol structure.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, a new peak at 289.9 eV assigned to C−Li bond emerges, which may be originated from the lithiation reaction or Li + ion insertion in condensed aromatic structures. Meanwhile, three peaks are also observed in the O1s spectrum (Figure 6b), corresponding to O−Li (531.1 eV), C−O (532.2 eV) and C=O (533.5 eV), respectively, [5a] further suggesting the formation of lithium enol structure.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, the lithiation process is further certified by XPS spectra analysis. As presented in Figure 6a, after the deeply discharge to 0.01 V, the C1s spectrum can be divided into five peaks, located at 284.3, 284.9, 285.8, 287.2 and 289.9 eV, ascribing the C=C, C−C, C−O/C−S, C=O and C−Li bonds, respectively [5a,16] . The C=O bond almost disappears and the appearance of C−O bond is attributed to the evolution of C=O to C−O−Li for the Li‐ion insertion.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] The electrochemical activities of organic electrode materials mainly depend on their well-designed functional groups (e.g., C═O, C═N, N═N, and S-S). [7] Therefore, many organic materials containing these functional groups were synthesized and applied as electrode materials, such as conductive polymers (e.g., polyacetylene, [8] polyphenyl, [9] polyaniline, [10] and polyimide [11] ), conjugated carbonyl compounds (e.g., quinones [12] and ketones [13] ), and so on. These organic materials presented outstanding electrochemical performances because of their multielectron transfer and structure engineering properties.…”
Section: Introductionmentioning
confidence: 99%
“…28−33 Modified PTO structures were employed in the designed cathode materials as the main chain, 30,34 side group, 28 or covalent organic framework (COF)/covalent organic polymer(COP). 29,31,32 Although one of the most used techniques to cope with the dissolution problem is the polymer formation, to the best of our knowledge only one study was reported in which polymethacrylate as a linear organic polymeric chain bearing PTO units was synthesized that exhibited the remarkable charge− discharge properties as a Li-ion cathode material. 28 Thus, we believe there is still room for improvement of modified PTO materials to be employed as cathode active materials in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the resulting inorganic−organic hybrid polymer (poly[(bis(2-amino-4,5,9,10-pyrenetetraone)]phosphazene (PPAPT) is designed as inherently halogen-free, insoluble, and flame retardant properties with high thermal stability because of the nature of the polyphosphazene derivatives. PPAPT was characterized by using appropriate standard spectroscopic methods (i.e., 31 P NMR (nuclear magnetic resonance) spectroscopy, FT-IR (Fourier-transform infrared spectroscopy), DSC (differential scanning calorimeter), and TGA (thermogravimetric analysis), and the electrochemical performance as a Li−ion battery cathode material was evaluated. Later, the lithium-ion storage mechanism of PPAPT was investigated by ex situ FT-IR, X-ray photoelectron spectroscopy (XPS) analyses, and density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%